PERFORMANCE EVALUATION OF AMMONIUM-BASED IONIC LIQUIDS AS THERMODYNAMIC GAS HYDRATE AND CORROSION INHIBITORS - ZOHAIR, SYED ALI QASIM (2021)
In oil and natural gas transmission pipelines, corrosion and formation of gas hydrates can lead to severe safety and economic losses.